(untitled) (Polish Yearbook of International Law, 2016)
The Maritime Labour Convention (MLC 2006) entered into force in 2013. The MLC 2006 aims at creating a single, coherent global instrument, consolidating existing International Labour Organisation conventions, and as well constitutes one of the main international maritime instruments of the International Maritime Organization, together with the International Convention for the Safety of Life at Sea (SOLAS), the International Convention for the Prevention of Pollution From Ships (MARPOL) and the International Convention on Standards of Training, Certification and Watchkeeping for Seafarers (STCW). Seafarers are entitled to lodge complaints on board a ship in case of non-compliance with the legal standards, procedures, or guidelines set forth in the MLC 2006, including seafarers’ human rights. The complaint system must include safeguards against victimisation. In 2015, the regulations of the MLC 2006 were implemented into a new Polish Act on Maritime Labour (MLA 2015). One of the most innovative aspects of the MLA 2015, as far as ILO Conventions are concerned, is the certification of seafarers’ living and working conditions on board ships, regulated in Chapter 8 of the Act (entitled: MLC documents and inspections and controls of the ship), as well as the on-board complaint procedure described in a detailed manner in Chapter 9 of the new Act.